Pencegahan Pencemaran Lingkungan dari Limbah Plastik dengan Pelatihan Pembuatan Ecobrick - Hartati, Wahjuni; Maula, Athiyatul; Ananta, Dita Amelia; Indriyanti, Gusti; Utomo, Faisal Prasetya; Rahayu, Indah; Larissa, Astrid Attha (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2024)
Adiwiyata schools are part of a program encouraging the creation of knowledge and awareness among school residents in environmental conservation. SMP Negeri 1 Sangasanga is one such school with an Adiwiyata program; however, significant plastic waste is still found around the school environment. Ecobrick represents a creative and innovative effort to address the problem of plastic waste pollution. The objectives of this activity are: 1. To raise awareness among students of SMP Negeri 1 Sangasanga about the impact of plastic pollution on the environment and the importance of sustainable plastic waste management; 2. To train students in making ecobricks as a creative solution to reduce plastic waste and transform it into a useful resource; 3. To integrate ecobrick production into school activities to foster a culture of waste management and environmental awareness among students. The methods used include socialization of ecobrick introduction, explanation of ecobrick making, and practice in assembling ecobricks into products as a form of plastic waste utilization. The results obtained from this activity show that students have gained knowledge and skills to process plastic waste into useful products through ecobrick, such as chairs